Weed Control in Bulb Crops (Onion, Leek, Garlic, Shallot) - William M. Stall (EDIS)
Revised! HS-193, a 3-page fact sheet by William M. Stall, describes effective weed management techniques for onions, leek, garlic, and shallots in Florida and provides a table of listing herbicides available to growers for chemical weed control of bulb crops. This publication updates the 2003 tables to reflect current recommendations. Published by the UF Department of Horticultural Sciences, October 2006.